PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PELABUHAN INDONESIA III (PERSERO) TERMINAL PETI KEMAS SEMARANG - Prasetiyo, Catur; Pradhanawati, Ari; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Business companies need in managing factors labor. Problems related to the performance of labor are the low. The factors that can influence the occurrence of performance is motivation, work satisfaction, the level of stress, the physical condition, work, a system of compensation and workplace there are to research performance evaluation of the employee who decline and absentee an increase in the presence of an employee ( alpa and permit ). The purpose of this research to find out the influence of compensation, motivation and workplace work on the performance of an employee of PT. Pelabuhan indonesia III ( persero ) container terminal semarang. Type research used in this research is explanatory research with 64 respondents taken using a technique the sampling method of accidental. Data collection techniques using interviews and questionnaires. The validity of test data analysis using techniques, a test of reliability, regression analysis as well as simple and double t test and test with the assistance spss 20.0 f. The results of research suggests that compensation effect on employee performance, the motivation of employees and influential work on the performance impact on the performance of employees work environment. Compensation, the motivation of work and work environment jointly effect on employee performance. Compensation, motivation of work and work environment jointly impact on employee performance. It is suggested that PT. Pelabuhan indonesia III ( persero ) container terminal semarang can give overtime wages and benefits that right, position promotion opportunity to all employees, give a kind of intensive training and sustainable, seminar-seminar themes motivation of work, as well as undertaking controlling to his employees about any employee performance already performed and occasional give a kind of briefing ( briefing ) directly to every employee who had a low that the future is expected to reduce the level to make mistakes and to cultivate initiative and improve employees to finish work on time, as well as companies pay more attention to work environment by increasing employment facilities, comfort and security work so can support operating the company.